Natural law and the rights of nature – in search of more effective environmental protection - Kowalska, Samanta (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2023)
The paper discusses innovative legal regulations that may contribute to increasing standards ofenvironmental protection. In the face of increasing nature degradation and climate change, current protection measures are insufficient. The dysfunction of the political system, international institutionalisation, and existing legal regulations, result in the strengthening of the global economy instead of increasing the extent of activities aimedattheprotection of nature. It is argued that the concept of natural law, which focuses on the protection of human rights, is not the same as the rights of nature. However, the analysis of the origins and axiological and legal assumptions of boththese concepts allows us to formulate the conclusion that both can form a common ethical perspective needed in order to protect the community of life on Earth. The aim of the considerations is to discuss the concept of the rights of nature, which are the basis for shaping the new environmental ethics. Appealing to common axioms, the idea of the rights of nature favours overcoming the limitations resulting from property law and the currently dominant economic and utilitarian factors. The paper arguesthat the environmentally-profiled rights of nature can become an ally in environmental protection.